Sosialisasi dan Edukasi: Membangun Kesadaran Anti-Bullying untuk Generasi Muda - Andini Nurul Syahfitri; Jasmine Az-zahra; Lutfi Hasbulloh; Muhammad Haidar Pasha; Sultan Novaliyana Putra (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Bullying and juvenile delinquency are social phenomena that have serious implications for students’ psychological, emotional, and social development, while also affecting the overall school climate and the quality of future generations. These conditions necessitate systematic and sustainable preventive efforts. The socialization program conducted at SMP Syamsul Ulum, Cigending, Ujung Berung District, Bandung City, was organized in response to this need, with the primary aim of enhancing students’ awareness, knowledge, and skills in preventing bullying and juvenile delinquency. The program was implemented through interactive socialization methods, participatory discussions, and continuous mentoring designed to encourage active student engagement. The results demonstrated a significant improvement in students’ understanding of the definitions, forms, impacts, and handling strategies related to bullying and juvenile delinquency. Moreover, positive behavioral changes were observed, including reduced conflict, improved healthy communication, and the growth of mutual respect among students. A symbolic activity involving colorful handprints on a banner served as a collective declaration of commitment to combating bullying. Overall, the program proved effective in fostering a safe, conducive, and supportive school environment. Therefore, similar initiatives are strongly recommended for replication in other schools to strengthen the character and integrity of Indonesia’s youth.